Peran Return on Asset dalam Memoderasi Hubungan Biaya Operasional Pendapatan Operasional, BI Rate, dan Capital Adequacy Ratio Terhadap Persentase Bagi Hasil Deposito Mudharabah Pada Bank Umum Syariah di Indonesia - Wahyu Putri Anggreani; Taufikur Rohman (Departement of Sharia Economics, Faculty of Islamic Economics and Business, Universitas Islam Negeri K.H Abdurrahman Wahid Pekalongan, 2022)
This study to determine the role of Return On Assets (ROA) in the relationship between Operational Costs from Operating Income (BOPO), BI Rate, and Capital Adequacy Ratio (CAR) to the percentage of profit sharing on mudharabah deposits at Islamic Commercial Banks in Indonesia at 2015-2019 period. This study uses field research with a quantitative approach to Islamic commercial banks registered with the Financial Services Authority as the population in the form of panel data. This study uses multiple linear regression testing techniques. The results showed that the BOPO and BI Rate showed that this variable had no significant positive effect on the percentage of profit sharing for mudharabah deposits. CAR shows that this variable has a negative and significant effect on the percentage of profit sharing for mudharabah deposits. Based on the Moderated Regression Analysis (MRA) test, the results show that ROA can moderate the relationship between the BOPO variable and the percentage of profit sharing for mudharabah deposits. ROA cannot moderate the relationship between the BI Rate variable and the CAR variable on the percentage of profit sharing for mudharabah deposits.